A comparison of neural net and conventional techniques for lighting control - Dodier, Robert; Lukianow, Diane; Ries, James; Mozer, Michael C. (Zielona Góra: Uniwersytet Zielonogórski)
We compare two techniques for lighting control in an actual room equipped with seven banks of lights and photoresistors to detect the lighting level at four sensing points. Each bank of lights can be independently set to one of sixteen intensity levels. The task is to determine the device intensity levels that achieve a particular configuration of sensor readings.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka